Genetic diversity of ayeyarmin mutant rice population revealed by quantitative traits - Zin, Thiri; Htwe, Nyo Mar; Mon, Hsu Yi; Thu, Moe Kyaw; Htun, Than Myint (Applied Research in Science and Technology, 2023)
One of the most important aspects of selecting genotypes with desirable characteristics for a successful breeding program is knowledge of the nature and magnitude of genetic variability. The goal of this study was to estimate the level of genetic divergence among mutant rice genotypes. During the 2020 dry season, a field experiment was carried out using 550 mutant lines with parent Ayeyarmin. The experiment was carried out using a simple CRD design. Six divergent groups were discovered by cluster analysis. Cluster I had the highest cluster mean for grain yield per plant, and the majority of the plants in these clusters resembled the parent Ayeyarmin. Cluster V, which had the fewest mutant lines (9), exhibited dwarf stature, short growth duration, fewer effective tillers per hill, and moderate yielding varieties. Cluster VI, which contained 11 mutant lines, had the most effective tillers per hill and the longest panicle length, both of which were appropriate for yield improvement. Cluster V had the greatest intra-cluster distance (5.77). Cluster V and IV had the greatest inter-cluster distance, followed by Cluster III and V, Cluster II and V, Cluster I and V, and the smallest between Cluster I and IV. Hybridization of Cluster I with V, Cluster V and VI could result in genotypes with desirable characteristics such as dwarf stature, short growth duration, and high yielding rice. The first three eigenvalues were found to have 62% variation using principal component analysis (PCA). Because of the high genetic variability in this mutant rice population, selection could be used to obtain desirable genotypes.